A proposed definition of microbiota transplantation for regulatory purposes. (4th May 2017) - Hoffmann, Diane E.; Palumbo, Francis B.; Ravel, Jacques; Rowthorn, Virginia; von Rosenvinge, Erik
ABSTRACT: The advent of fecal microbiota transplantation (FMT) and the prospect of other types of microbiota transplants (MT), e.g. vaginal, skin, oral and nasal, are challenging regulatory agencies. Although FDA is regulating FMT (as a biologic), there is currently no widely accepted or agreed upon scientific or legal definition of FMT or MT. The authors report on discussions regarding a definition of MT that took place among a working group of stakeholders convened under a National Institutes for Allergies and Infectious Diseases grant to address the regulation of MT. In arriving at a definition, the group considered the 1) nature of the material being transplanted; 2) degree of manipulation of the transferred materials prior to implantation; 3) ability to characterize the transplanted product using external techniques; and 4) origin of the stool product (single vs multiple donors).